2016
DOI: 10.1515/znc-2015-0119
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of antitumor activity of new rotundic acid acylhydrazone derivatives

Abstract: In light of the important antitumor activity of acylhydrazone compounds and based on our previous study, 18 new rotundic acid (RA) acylhydrazone derivatives were synthesized. All of the compounds were characterized by their spectroscopic data. The antiproliferative activity of the compounds was evaluated in vitro via the MTT method in three tumor cell lines, including A-375 (human malignant melanoma cells), SPC-A1 (human lung adenocarcinoma) and NCI-H446 (small cell lung cancer). The results showed that the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…1A). For this experiment, cells were seeded in wells of 96-well plate and maintained in culture medium for 24 h. The cells were then treated with test compounds (5,10,20, 50 mM concentration of each compound) for 24 h. As indicated in Fig. 1B, the compounds A0, A1, A2, A3, A4, A5, A7 and A8 showed that the dependence of cell viability on concentration is clearly noticed.…”
Section: Cytotoxic Effects Of Acylhydrazone Compounds On Neuro-2a Cellsmentioning
confidence: 91%
See 1 more Smart Citation
“…1A). For this experiment, cells were seeded in wells of 96-well plate and maintained in culture medium for 24 h. The cells were then treated with test compounds (5,10,20, 50 mM concentration of each compound) for 24 h. As indicated in Fig. 1B, the compounds A0, A1, A2, A3, A4, A5, A7 and A8 showed that the dependence of cell viability on concentration is clearly noticed.…”
Section: Cytotoxic Effects Of Acylhydrazone Compounds On Neuro-2a Cellsmentioning
confidence: 91%
“…9,10 In recent years, researchers have found that acylhydrazone compounds exhibit many benecial biological activities, such as anti-bacterial, [11][12][13] anti-inammatory, [14][15][16] anti-viral 17,18 and anti-tumor activities. [19][20][21] However, there are currently few studies on the neuroactivity of acylhydrazone compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Rotundic acid (RA), a plant-derived and ursane-type pentacyclic triterpene acid, was identified as a major active ingredient of IRC and has been shown to exert extensive pharmacological effects, including antimicrobial [ 3 , 4 ], anti-inflammatory [ 5 ], anticancer [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ], and lipid-decreasing effects [ 14 ]. It has also been proven to alleviate type 2 diabetes and its complications by improving the composition of the gut microbiota [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulative data concerning TCM have shown marked activity with regard to the effects on the tumor cell death pathway, which can guide tumor treatment decisions and clinical management (9). Currently, compounds with unique chemical entities that are derivatives of natural medicines are a considerable resource for the development of novel medicines (10). Rotundic acid (RA; Fig.…”
Section: Introductionmentioning
confidence: 99%